2004
DOI: 10.1074/jbc.m310012200
|View full text |Cite
|
Sign up to set email alerts
|

UTP Transactivates Epidermal Growth Factor Receptors and Promotes Cardiomyocyte Hypertrophy Despite Inhibiting Transcription of the Hypertrophic Marker Gene, Atrial Natriuretic Peptide

Abstract: In neonatal rat ventricular myocytes, activation of receptors that couple to the G q family of heterotrimeric G proteins causes hypertrophic growth, together with expression of "hypertrophic marker" genes, such as atrial natriuretic peptide (ANP) and myosin light chain 2 (MLC2). As reported previously for other G q -coupled receptors, stimulation of ␣ 1 -adrenergic receptors with phenylephrine (50 M) caused phosphorylation of epidermal growth factor (EGF) receptors as well as activation of ERK1/2, cellular gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
0
18
2
Order By: Relevance
“…The immunoblot is representative of three independent experiments. P2Y 1 R stimulates EGFR-mediated mitogenesis cells, including PC12 cells (Soltoff, 1998), MCF7 breast cancer cells (Wagstaff et al, 2000), astrocytoma cells transfected with P2Y 2 R (Liu et al, 2004), cardiomyocytes (Morris et al, 2004) and A549 lung cancer cells (Schafer et al, 2003). However, these studies analyzed neither the effects of apyrase nor the congruency between the lifetime of P2Y 2 R stimuli and proliferation requirements.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The immunoblot is representative of three independent experiments. P2Y 1 R stimulates EGFR-mediated mitogenesis cells, including PC12 cells (Soltoff, 1998), MCF7 breast cancer cells (Wagstaff et al, 2000), astrocytoma cells transfected with P2Y 2 R (Liu et al, 2004), cardiomyocytes (Morris et al, 2004) and A549 lung cancer cells (Schafer et al, 2003). However, these studies analyzed neither the effects of apyrase nor the congruency between the lifetime of P2Y 2 R stimuli and proliferation requirements.…”
Section: Discussionmentioning
confidence: 96%
“…P2Y 2 R is the only other P2YR subtype previously described to mediate cell proliferation by transactivating the EGFR (Liu et al, 2004;Morris et al, 2004;Schafer et al, 2003;Soltoff et al, 1998;Wagstaff et al, 2000). P2Y 2 R is mainly activated by ATP and UTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine and its specific receptors were not evaluated as it did not elicit a Ca 2+ wave, induce phosphorylation of ERK or play a role in cell migration in corneal epithelial cells (Klepeis et al, 2004). In cardiomyocytes, the nucleotide UTP has been shown to transactivate EGFR (Morris et al, 2004). Still other work has shown that activation of P2Y2 receptors in PC12 cells induced EGFR in a PKC dependent manner (Soltoff 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Ang II has been shown to transactivate the EGFR in isolated cardiomyocytes 36 and whole hearts, the latter study suggesting that ADAM12 was responsible for HB-EGF shedding and subsequent cellular hypertrophy. 37 Although not necessarily the sole signaling pathway by which GPCRs stimulate cardiomyocyte hypertrophy, urotensin II, 38 endothelin-1, 37 purinergic P2Y, 39 and ␣1-adrenergic 39 receptors all stimulate cardiac enlargement via an ErbB receptordependent mechanism. Studies in renal and VSMCs further illustrate the general importance of transactivation in vascular biology.…”
Section: Transactivation Of Egf Receptors: a Common Pathway For Gpcr-mentioning
confidence: 99%